POLA KOMUNIKASI DI DALAM PENYELESAIAN KONFLIK PERTEMANAN JARAK JAUH - Anni Rahmawati; Vitalia Adisti (Triwikrama: Jurnal Ilmu Sosial, 2025)
Communication is key in maintaining social relationships, including long-distance friendships which are common in this era of digitalization and globalization. This research discusses communication patterns in resolving long-distance friendship conflict. The aim of this research is to determine communication patterns and ways of resolving conflict in long-distance friendships and to help provide an understanding of effective communication patterns in resolving conflict in long-distance friendships by focusing on effective strategies. This research uses a qualitative approach through in-depth interviews with someone who has experience in long-distance friendship relationships. From the results obtained through in-depth interviews with 10 sources, it shows that conflict can arise due to misunderstanding in receiving messages using instant communication media technology, like WhatsApp, Instagram and many more. However this obstacle can be overcome with several communication strategies accompanied by an attitude of openness, empathy, and responsiveness which are the main elements in creating healthy and harmonious relationships, even with the limitations of physical distance. Choosing communication media that is appropriate to the conflict at hand not only helps reduce the potential for misunderstandings, but also strengthens the understanding of perspectives between both parties, which is essential in the conflict resolution process.